DEVELOPMENT OF PREVENTION AND TREATMENT OF INFLAMMATORY DYSTROPHIC PERIODONTAL DISEASE IN WORKERS OF GYPSUM PRODUCTION PLANT WITH DISEASES OF THE UPPER RESPIRATORY TRACT - Norova M.B; Xabibova N.N (International Journal of Human Computing Studies, 2020)
Diseases of the oral cavity are a common pathology that leads to the loss of teeth, the formation of foci of chronic odontogenic infection and other disorders both in the maxillofacial region and in the body as a whole. Serious medical and social consequences of inflammatory periodontal diseases and the lack of noticeable positive changes in their mass prevention determine the need to deepen and concretize ideas about the etiology and pathogenesis of these diseases (Tsepov L. M. Nikolaev A. I., Mikheev N. A. et al., 2004).